2021
DOI: 10.1152/ajpregu.00027.2020
|View full text |Cite
|
Sign up to set email alerts
|

Chronic CNS-mediated cardiometabolic actions of leptin: potential role of sex differences

Abstract: Previous studies using male rodents showed the adipocyte-derived hormone leptin acts in the brain to regulate cardiovascular function, energy balance and glucose homeostasis. The importance of sex differences in cardiometabolic responses to leptin, however, is still unclear. We examined potential sex differences in leptin's chronic central nervous system (CNS)-mediated actions on blood pressure (BP), heart rate (HR), appetite, and glucose homeostasis in normal and type 1 diabetic rats. Female (n=6) and male (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“… 21 We also showed that these effects were mediated by the CNS since this dose of leptin infused intracerebroventricular does not increase circulating levels of leptin. 13 In addition, chronic intraperitoneal leptin infusion at the same dose infused intracerebroventricular in the present study (0.62 μg/h) did not alter food intake, body weight, blood pressure, heart rate, blood glucose, or insulin levels in male and female rats. 13 …”
Section: Discussionsupporting
confidence: 45%
See 4 more Smart Citations
“… 21 We also showed that these effects were mediated by the CNS since this dose of leptin infused intracerebroventricular does not increase circulating levels of leptin. 13 In addition, chronic intraperitoneal leptin infusion at the same dose infused intracerebroventricular in the present study (0.62 μg/h) did not alter food intake, body weight, blood pressure, heart rate, blood glucose, or insulin levels in male and female rats. 13 …”
Section: Discussionsupporting
confidence: 45%
“… 13 In addition, chronic intraperitoneal leptin infusion at the same dose infused intracerebroventricular in the present study (0.62 μg/h) did not alter food intake, body weight, blood pressure, heart rate, blood glucose, or insulin levels in male and female rats. 13 …”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations